Harvard business essentials : (Harvard Business School Press, 2002)
Hiring an all-star workforce and keeping it in place is a challenge for any organization. Packed with hands-on tips and tools, Hiring and Keeping the Best People offers managers comprehensive advice for hiring more effectively and increasing retention.